Students’ Creative Thinking in Semi-Complex Contexts: A Study of Mathematical Problem Construction - Rohmat Akbar Aji; Rizqita ‘alimatun Nisa’; Turmudi; Elly Susanti (Al-Qalam Institue, 2026)
This study aims to describe the creative thinking abilities of students in the semi-complex category when posing mathematical problems, focusing on fluency, flexibility, originality, and elaboration. The research employed a descriptive qualitative approach involving Madrasah Aliyah students selected based on a creative thinking ability test. Data were collected through problem-posing tasks and semi-structured interviews to explore students’ thought processes in depth. The findings reveal that students are able to generate several mathematical problems with varied structures and contexts, particularly demonstrating fluency and flexibility; however, they remain limited in terms of originality and depth of elaboration. The implications of this study highlight the need for instructional strategies that encourage deeper idea exploration, the use of open-ended stimuli, and reflective guidance to enhance students’ creative thinking quality in mathematical problem posing. Additionally, continuous practice and supportive learning environments that promote collaboration, discussion, and real-world contexts are essential to foster more original ideas and richer elaboration, contributing to meaningful improvement in mathematics learning at the secondary education level.